Improved utilization of phosphorous from sewage sludge (as Fertilizer) after treatment by Low-Temperature combustion. (October 2018) - Meng, Xiangdong; Huang, Qunxing; Gao, Huaping; Tay, Kangrou; Yan, Jianhua
Highlights: Low-temperature combustion enriches phosphorus in sludge better than incineration. High O2 concentration during low-temperature combustion promotes Ca-P generation. Low-temperature combustion increases P-bioavailability in sludge bottom ash. Phosphorus in sludge after low-temperature combustion is in form of orthophosphate. Leaching of heavy metals in low-temperature combustion ash is reduced. Abstract: The utilization of phosphorus from sewage sludge is an important method used to solve the shortage of phosphorus resources in the world. However, high levels of toxic compounds and low phosphorus bioavailability in sewage sludge are the main factors limiting its direct agricultural use. This paper proposes a low-temperature combustion method that can enrich the phosphorus in sludge ash. Low temperature-treated sewage sludge ash (LTSA) at different oxygen concentrations (20%, 60%, 100%) were obtained through a specific experimental device. Then, the species and leaching characteristics of phosphorus in LTSAs were analyzed and compared with pyrolysis sewage sludge char (PSSC) and incinerated sewage sludge ash (ISSA). Results show that low-temperature combustion of sludge increased the total phosphorus content in the bottom ash by 45.6%, and the bioavailable phosphorus content increased 2.9 times. Further, by increasing the concentration of oxygen while carrying out low-temperature combustion of sludge, part of the non-apatite inorganic P was converted to apatite P (AP), resulting in a 46.3% increase in AP in the sludge. Low-temperature combustion can also convert heavy metals (Cd, Cr, Cu, Pb, and Zn) in the sludge from an easily leachable form (acid extractable fraction and reducible fraction) to a stable form (reducible fraction) and decrease the leaching of heavy metals. Leaching of Cr and Cu decreased by 97.56% and 98.52%, respectively.